Linux security and hardening (Manning Publications, 2022)
Keep yourself and your company out of the news by protecting your Linux systems from hackers, crackers, and attackers! This course will not only teach you the security concepts and guidelines that will keep your Linux servers safe, it will walk you through hardening measures step-by-step. By the end of this course you will be able to tighten up the security on any Linux system. You'll learn the security weaknesses of the Linux operating system and be given step-by-step instructions on how to protect those weaknesses. You'll even learn some security concepts that apply to information security as a whole while focusing on the Linux specific issues that require special consideration.